On pupils' reactions to the use of open-ended problems in mathematics - Pehkonen , Erkki (NOMAD Nordic Studies in Mathematics Education, 1995)
This article will focus on the preliminary results of one experimental class from the three-year research project "Open tasks in mathematics", which has been carried out in junior high schools during the years 1989-92 in Helsinki (Finland). The experiment groups used open-ended problems (problem fields) regularly, i.e. once a month, within their normal teaching. The main results from one class (N = 18) were as follows: The pupils liked most of the problem fields used. Their mathematical views did not change statistically significantly, but the non-significant changes in questionnaire ratings, classroom observations and the teacher's evaluations indicate that there was a change, and the change was in most cases positive.